Hypoglycaemia following removal of phaeochromocytoma: case report and review of the literature. Issue 682 (August 1982) - Chambers, Stephen; Donald, Richard A.; Espiner, Eric A.; Nicholls, M. Gary
Abstract : Hypoglycaemia may complicate removal of a phaeochromocytoma, but its pathogenesis is not well understood. The sixth such case in the world literature is reported together with details of glucose tolerance testing and hormone levels before and after extirpation of an adrenal phaeochromocytoma. The mechanism of hypoglycaemia probably relates to a sudden decrease in circulating catecholamines which allows a rebound increase in insulin release and in peripheral glucose uptake. It is suggested that blood sugar levels should be monitored routinely after surgery for phaeochromocytoma.